OTS 2024 Sodobne informacijske tehnologije in storitve: Zbornik 27. konference - Lahovnik, Tadej; Vrbančič , Grega; Ambrožič, Vojko; Krajnc, Andrej; Štok , Bojan; Kliček, Nina; Šestak, Martina; Turkanović , Muhamed; Četina, Luka; Pavlič , Luka; Škarabot, Mihael; Granda , Alen; et al. (2024)
OTS 2024 Advanced Information Technologies and Services: Conference Proceeding of the 27th Conference. In the proceedings of the twenty-seventh OTS 2024 conference, the contributions of experts in the field of informatics are published, in which new insights and trends in the development, implementation, adaptation and management of information solutions are presented, as well as concrete successful approaches and good practices. Contributions address the areas of contemporary architectural challenges, classical, generative and deep artificial intelligence, modern web or mobile user interfaces, as well as traditional, serverless and decentralized cloud backend systems. The topics of the contributions also include providing an appropriate scalable environment for them and automating testing, quality measurement and delivery by proactively addressing the most common cyber attacks. The red thread of the contributions is represented by data technologies, which are represented in the form of classic databases, data lakes and efficient collection, processing and visualization of big data. The contributions thus continue to enable a better connection between IT experts, informaticists, architects and developers of IT solutions and services, as well as the academic sphere and business.
Keywords: informatics; ICT technologies; software engineering; ICT solutions; information systems; digital transformation; development of mobile and web solutions; cloud architectures; data technologies; business intelligence; artificial intelligence and machine learning; big data and data streams; methods of agile development; blockchain technologies; cybersecurity